Development of an Ethnomathematics-Based Pop-Up Book Oriented Toward Elementary Students’ Conceptual Understanding of Mathematics - Ni Putu Eka Satvika Devioni; Muhammad Erfan; Asri Fauzi (MASI Mandiri Edukasi, 2025)
Low levels of students’ conceptual understanding of mathematics pose a significant barrier to mastering subsequent topics and developing other essential mathematical skills. One contributing factor frequently associated with this issue is the limited variety and contextual relevance of instructional media used in the classroom. This study aims to develop an ethnomathematics-based pop-up book to enhance elementary students’ conceptual understanding of three-dimensional geometric shapes, evaluated in terms of its validity, practicality, and effectiveness. The research employs a development methodology following the ADDIE model, which consists of five key stages: Analysis, Design, Development, Implementation, and Evaluation. The participants in this study were 25 sixth-grade students at SDN 1 Bayan. Data were collected through tests and questionnaires and analyzed using qualitative and quantitative approaches. The findings revealed that: (1) the media expert validation yielded a score of 70, categorized as “highly valid”; (2) the content expert validation resulted in a score of 69, also rated “highly valid”; (3) small group trials conducted by teachers and students obtained scores of 53 and 56.8 respectively, both categorized as “highly practical”; (4) the large group trial yielded a score of 54.4, also falling within the “highly practical” category; and (5) the effectiveness test using the Wilcoxon Signed Rank Test produced a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest results. These results confirm that the ethnomathematics-based pop-up book is valid, practical, and effective in improving sixth-grade students’ conceptual understanding of three-dimensional geometry. Integrating ethnomathematical elements is designed to assist teachers in delivering more engaging and interactive instruction, thus enabling students to comprehend geometric concepts better through cultural contexts.